Effect of Allicin on Tamoxifen-sensitive MCF-7 Breast Cancer Cells - P Rahimi-Moghaddam; H Hashemi-Setobadi; F Ghazinejhadian- Shooshtari (Institue of Medicinal Plants, ACECR, 2015)
Background: One-eighth of women will develop breast cancer in their lifetime, resulting in approximately annual one million women worldwide with breast cancer. Approximately 70% of breast cancers are positive for estrogen receptor alpha (ER-). The presence of ER- receptor is associated with better prognosis and usually indicates that the anti-estrogen drugs such as tamoxifen can be useful in the treatment. Nevertheless, a significant number of ER--positive breast cancers does not respond to tamoxifen. Causes of resistance to tamoxifen and how to sensitize to tamoxifenis not yet known. Preliminary studies indicate that garlic and its derivatives such as allicin, have anti-cancer effects. Objective: This study aims to investigate the inhibitory effect of allicin on tamoxifen-sensitive MCF-7 cells. Methods: To investigate this theory, the effect of allicin on tamoxifen-sensitive cells (MCF-7), and -resistant cells (Sk-Br-3) in the presence and absence of tamoxifen and 17- estradiol were studied. The cell viability was assessed using MTT assay at 24, 48 and 72 hours. Results: The study revealed that allicin in MCF-7 cells enhances the effectiveness of tamoxifen in the presence and absence of 17-b estradiol. Conclusions: Allicin as an adjunct to tamoxifen can sensitize breast cancer cells to tamoxifen.